The Effectiveness of Word Wall Strategy to Improve Students Vocabulary to the 7th Graders of SMP Negeri 1 Jepara - Dewi Kurnia Sari; Senowarsito; Fitri Yulianti (ELITE JOURNAL, 2023)
ABSTRACTVocabulary is important for language knowledge. This study is to find out whether any significant difference between vocabulary ability of the students who are taught with word wall strategy and without word wall strategy to the 7th graders of SMP Negeri 1 Jepara. Quasi-experimental research was used in this study method. In this study, the writer collects the data by using the tests. The writer uses the statistical calculation with SPSS in data analyzed. The sample of this research is two classes from seventh grade. One class for the experimental class and one class for the control class. Each class has 32 students. As a result, it can be witnessed from the mean of pre-test and pos-test. In pre-test result experimental class is 68, while control class is 65. After being given treatment, experimental class is 84, while control class is 65. Moreover, the hypothesis result showed that Ha is accepted. Because T-value was higher than the table's critical value (5.996> 1.998), it indicates that there was a significant difference in the students' vocabulary ability using word wall strategy and without using word wall strategy. Keywords: Vocabulary, Word Wall, English Learning